Diagnostic Accuracy of Vibration Controlled Transient Elastography as Non-invasive Assessment of Liver Fibrosis in Patients with Non-alcoholic Fatty Liver Disease. - Salehi, Hossain; Salehi, Amir Mohammad; Ghamarchehreh, Mohammad Ebrahim; Khanlarzadeh, Elham; Sohrabi, Masoud Reza (Middle East Journal of Digestive Diseases, 2023)
Background: Liver biopsy remain as the gold standard for diagnosing hepatic fibrosis; however, it has some limitations, such as life-threatening complications, low acceptance by the patients, and variations in the related sample. Therefore, there is a need for the development of non-invasive investigations for diagnosing hepatic fibrosis. Vibration-controlled transient elastography (VCTE) is one of these non-invasive methods. Methods: This study included 73 patients suffering from non-alcoholic fatty liver disease (NAFLD) who were older than 18 years. The patients underwent VCTE at the Baqiatallah and Firoozgar hospitals. Then, they underwent a liver biopsy by an experienced radiologist in the same hospital. A receiver operating characteristic (ROC) curve of different fibrosis stages was used to evaluate the VCTE verification. Results: VCTE could detect any fibrosis levels (stage 1 and higher) with an area under the ROC curve (AUROC) of 0.381. Moreover, it detected stage 2-4 fibrosis with an AUROC of 0.400, stage 3-4 fibrosis with an AUROC of 0.687, and stage 4 fibrosis with an AUROC of 0.984. Conclusion: The VCTE has high clinical validity in diagnosing the advanced stages of fibrosis (stages 3, 4) and can be a suitable alternative to the invasive method of liver biopsy with high reliability.